Developing Speaking Skills through Storytelling: A Case Study of Sixth Grade Students at MI Nurul Huda Pondok Jaya (Universitas Pamulang, 2022)
This study aims to explore the use of storytelling as a technique to develop students' speaking skills. Specifically, it investigates three key aspects: (1) the types of storytelling topics that effectively enhance speaking abilities, (2) the instructional activities employed by the teacher to teach speaking through storytelling, and (3) the students' responses to the use of storytelling in the classroom. To achieve these objectives, a qualitative research method was applied, where the analysis is presented in a descriptive, textual form. Data were collected through direct observation of classroom activities and interviews with both the teacher and the students. The observations allowed for an in-depth understanding of how storytelling is integrated into the speaking curriculum, while the interviews provided insights into the students’ experiences and perceptions. The findings of this study reveal that storytelling is an effective technique for teaching speaking. It helps students become more engaged and active participants in the classroom. Through storytelling, students were encouraged to use their own words to narrate, describe, and express ideas, which in turn built their confidence in speaking English. The interactive nature of the storytelling activities also fostered a positive learning environment, as students enjoyed the process of listening to and telling stories. This enjoyment was crucial in motivating them to practice speaking more frequently and confidently. Overall, the study concludes that storytelling is a valuable tool for developing speaking skills, as it not only helps students practice language but also nurtures their creativity and enhances their ability to communicate in a more relaxed, supportive atmosphere. The findings underscore the importance of integrating engaging, communicative methods like storytelling into language teaching, particularly when aiming to improve students' speaking proficiency.